Meta-analysis of exome array data identifies six novel genetic loci for lung function - Jackson VE; Latourelle JC; Wain LV; Smith AV; Grove ML; Bartz TM; Obeidat M; Province MA; Gao W; Qaiser B; Porteous DJ; Cassano PA; et al. (My University, 2022)
Background: Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease.
Methods: We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV1), forced vital capacity (FVC) and the ratio of FEV1 to FVC (FEV1/FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals.
Results: We identified significant (P<2·8x10-7) associations with six SNPs: a nonsynonymous variant in RPAP1, which is predicted to be damaging, three intronic SNPs (SEC24C, CASC17 and UQCC1) and two intergenic SNPs near to LY86 and FGF10. Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including TYRO3 and PLAU.
Conclusions: Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.